University-Community Engagement Conference – UCEC2017 - APUCEN, Asia-Pacific University-Community Engagement Network (2017)
University-Community Engagement goes beyond mere outreach, as universities seek mutually beneficial relationships with communities to address community issues and needs with a commitment to sharing and reciprocity which embraces two-way partnerships. UCEC is the biennial conference promoted by the Asia-Pacific University-Community Engagement Network (APUCEN) and co-hosted by their members. This is the first UCEC to be held in Japan.